1999
DOI: 10.1038/sj.bjc.6693403
|View full text |Cite
|
Sign up to set email alerts
|

Loss of chromosome 10 is an independent prognostic factor in high-grade gliomas

Abstract: Gliomas are the most frequently occurring central nervous system (CNS) tumours and include astrocytomas, anaplastic astrocytomas and glioblastoma multiforme. They are severely disabling, producing symptoms of headaches, fits, confusion, personality changes and neurological deficits which impair the patients' quality of life. Despite advances in the diagnosis and treatment of gliomas the prognosis remains poor, with only 10-15% survival for patients with high-grade gliomas at 30+ months (Brada et al, 1998). Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 32 publications
3
37
0
1
Order By: Relevance
“…Losses from chromosome 10 have been shown to be a negative prognostic factor in high-grade astrocytomas (Balesaria et al, 1999;Tada et al, 2001;Ohgaki et al, 2004) and in oligodendroglial tumors (Thiessen et al, 2003;Trost et al, 2007). In this study, the minimal common overlapping area in 10q26.13-26.2 was lost in 71.4% of glioblastomas.…”
Section: Discussionsupporting
confidence: 46%
“…Losses from chromosome 10 have been shown to be a negative prognostic factor in high-grade astrocytomas (Balesaria et al, 1999;Tada et al, 2001;Ohgaki et al, 2004) and in oligodendroglial tumors (Thiessen et al, 2003;Trost et al, 2007). In this study, the minimal common overlapping area in 10q26.13-26.2 was lost in 71.4% of glioblastomas.…”
Section: Discussionsupporting
confidence: 46%
“…31,32 Several molecular markers have been proposed, including LOH of chromosome 10 and the overexpression of EGFR--both of which are correlated with a poor prognosis. [33][34][35] To learn more about the roles of SOX5 antibody responses in GBM patients, we compared the survival of antibody-positive patients with that of antibody-negative patients. Kaplan-Meier plotting showed that the survival of GBM patients with SOX5 IgG was significantly prolonged, compared to that of SOX5 IgG-negative patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 They are present in the large majority of patients with glioblastoma multiforme (GBM), the most malignant glioma. Recent evidence suggests that complete losses of one copy of chromosome 10 are more frequent in primary GBM and partial losses in secondary GBM.…”
Section: Dear Sirmentioning
confidence: 99%